Development and validation of a scale of attitudes towards alcohol, alcoholism and alcoholics Construcción y validez de una escala de actitudes frente al alcohol, al alcoholismo y al alcohólico Construção e validação de uma escala de atitudes frente ao álcool, ao alcoolismo e ao alcoolista - Divane de Vargas; Margarita Antonia Villar Luis (Universidade de São Paulo, 2008)
The objective of this study was the construction and validation of a scale that would measure the attitudes towards alcohol, alcoholism and the alcoholic, called the Scale of Attitudes Towards Alcohol, Alcoholism and the Alcoholic. The face and content validations, as well as the factor analysis of the data obtained in a preliminary test with 144 nursing students resulted in a scale consisting of 96 items, divided into 5 factors: Attitudes towards the alcoholic person: care and interpersonal relations; Etiology; Disease; Repercussions deriving from alcohol use/abuse; Alcoholic beverages. The general scale presented a consistency level of 0.90. The resulting instrument is concluded to be a reliable tool to evaluate attitudes towards alcohol, alcoholism and alcohol addicts. Este estudio tuvo como objetivo construir y validar un instrumento de medida de Actitudes frente al Alcohol, al Alcoholismo y al Alcohólico: Escala de Actitudes frente al Alcohol, al Alcoholismo y al Alcohólico. La validez aparente y de contenido del instrumento, así como el análisis factorial de los datos de su aplicación preliminar a un total de 144 estudiantes de enfermería, resultaron en una escala compuesta por 96 ítems divididos en cinco factores agrupados bajo el nombre de Actitudes frente al alcohólico: el trabajo y las relaciones interpersonales; la Etiología; la Enfermedad; las Repercusiones provenientes del uso/abuso del alcohol; y, la Bebida alcohólica. La Escala general presentó una consistencia interna de 0,90; se concluyó que el instrumento construido se mostró confiable para la evaluar las actitudes frente al alcohol, al alcoholismo y al alcohólico. Este estudo teve como objetivo construir e validar instrumento de medida de atitudes frente ao álcool, ao alcoolismo e ao alcoolista (escala de atitudes frente ao álcool, ao alcoolismo e ao alcoolista). A validação aparente e de conteúdo do instrumento, bem como a análise fatorial dos dados de sua aplicação preliminar, realizada com amostra de 144 estudantes de enfermagem, resultou numa escala composta por 96 itens divididos em cinco fatores: atitudes frente ao alcoolista - o trabalho e as relações interpessoais; etiologia; doença; repercussões decorrentes do uso/abuso do álcool; a bebida alcoólica. A escala geral apresentou consistência interna de 0,90. Concluiu-se que o instrumento construído mostrou-se confiável para avaliação das atitudes frente ao álcool, ao alcoolismo e ao alcoolista.